1990
DOI: 10.1085/jgp.95.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional properties of two types of horizontal cell in the skate retina.

Abstract: Two morphologically distinct types of horizontal cell have been identified in the all-rod skate retina by light-and electron-microscopy as well as after isolation by enzymatic dissociation. The external horizontal cell is more distally positioned in the retina and has a much larger cell body than does the internal horizontal cell. However, both external and internal horizontal cells extend processes to the photoreceptor terminals where they end as lateral elements adjacent to the synaptic ribbons within the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…GABA release in horizontal cells is generally thought to occur by a transporter-mediated mechanism. This unconventional GABA release was first described in the amphibian and fish retina (Schwartz, 1982(Schwartz, , 1987Yazulla andKleinschmidt, 1982, 1983;Ayoub et al, 1984) where GABA transporters are expressed in horizontal cells and generate measurable currents (Malchow et al, 1990;Cammack and Schwartz, 1993;Dong et al, 1994). In agreement with this hypothesis, classic synaptic specializations were not observed in horizontal cell processes (Yazulla, 1995), except for human horizontal cells (Linberg and Fisher, 1988).…”
Section: Gaba Release In Horizontal Cellsmentioning
confidence: 52%
“…GABA release in horizontal cells is generally thought to occur by a transporter-mediated mechanism. This unconventional GABA release was first described in the amphibian and fish retina (Schwartz, 1982(Schwartz, , 1987Yazulla andKleinschmidt, 1982, 1983;Ayoub et al, 1984) where GABA transporters are expressed in horizontal cells and generate measurable currents (Malchow et al, 1990;Cammack and Schwartz, 1993;Dong et al, 1994). In agreement with this hypothesis, classic synaptic specializations were not observed in horizontal cell processes (Yazulla, 1995), except for human horizontal cells (Linberg and Fisher, 1988).…”
Section: Gaba Release In Horizontal Cellsmentioning
confidence: 52%
“…4B). The currents activate rapidly at depolarizing voltages Ն Ϫ20 mV, they deactivate quickly after membrane repolarization, and the I-V relation appears to have a profile similar to that of the delayed rectifier (e.g., the Kv3 channel family) observed in many other preparations (5,6).…”
Section: Bipolar Cells In the Vertebrate Retina Are Second-order Neurmentioning
confidence: 72%
“…The procedure for obtaining isolated horizontal cells has been described in detail previously (Malchow et al, 1990). Briefly, eyes were enucleated from skate (Raja erinacea and Raja ocellata) that had been sedated on ice, and pithed both anteriorly and posteriorly.…”
Section: Cell Dissociationmentioning
confidence: 99%
“…Only the large external horizontal cells of the skate retina, viewed under phase contrast optics and readily identified by their characteristic morphology (Malchow et al, 1990), were used for this study. For voltage-clamp experiments, membrane currents were monitored using the whole-cell version of the patchclamp technique (Hamill et al, 1981), and details of the recording were reported previously (HaughScheidt, Malchow and Ripps, 1995).…”
Section: Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation